2019
DOI: 10.1136/bmjopen-2018-027790
|View full text |Cite
|
Sign up to set email alerts
|

Designing and pilot testing of a leadership intervention to improve quality and safety in nursing homes and home care (the SAFE-LEAD intervention)

Abstract: ObjectiveTo describe the design of a leadership intervention for nursing home and home care, including a leadership guide for managers to use in their quality and safety improvement work. The paper reports results from the pilot test of the intervention and describes the final intervention programme.DesignQualitative design, using the participation of stakeholders.MethodsThe leadership guide and intervention were designed in collaboration with researchers, coresearchers and managers in nursing homes and home c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(77 citation statements)
references
References 35 publications
3
73
0
1
Order By: Relevance
“…There is a need for collective reflexive spaces and arenas for home care managers to discuss patient safety. Our research has demonstrated how home care managers can take advantage of facilitated arenas and tools to support discussions of their role in developing a culture of patient safety (Johannessen et al, ). From a policy perspective, we recommend policy guidelines and regulations to enable making such efforts in healthcare organizations, by emphasizing the importance of transformational leadership for sound work environments and patient safety cultures and by providing resources to leadership and work environment interventions.…”
Section: Discussionmentioning
confidence: 98%
“…There is a need for collective reflexive spaces and arenas for home care managers to discuss patient safety. Our research has demonstrated how home care managers can take advantage of facilitated arenas and tools to support discussions of their role in developing a culture of patient safety (Johannessen et al, ). From a policy perspective, we recommend policy guidelines and regulations to enable making such efforts in healthcare organizations, by emphasizing the importance of transformational leadership for sound work environments and patient safety cultures and by providing resources to leadership and work environment interventions.…”
Section: Discussionmentioning
confidence: 98%
“…The data material was analyzed using directed content analysis approach according to predefined categories [18]. The predefined categories derived from theory, the OQ framework [17] and a further refinement by Johannessen [14]. The categories were structure (plan and structure for the organizations' quality work), coordination and organizational politics (interaction within the organization and between service levels), culture (create an organizational culture where quality is a common value), competence (continuous competence development in the organization),engagement (support and mobilize employees to create motivation in the quality improvement work), physical design and technology (implies premises, outdoor areas and the importance of home environment for quality improvement work), and external demands (awareness and decision related to social, political and economic factors such as regulatory requirements, national professional guidelines).…”
Section: Discussionmentioning
confidence: 99%
“…This paper is part of a larger project titled 'Improving Quality and Safety in Primary Care -Implementing a Leadership Intervention in Nursing Homes and Home care' (SAFE-LEAD) [12], based on an intervention implementing a leadership guide for managers over a period of 12 months in 2018-2019 [12]. The leadership guide comprises seven common quality challenges (structure, coordination/organizational politics, culture, competence, engagement, physical design/technology, external demands) in which the organizations work with and diagnose themselves [13,14]. In this paper, we map the status of the organizations in relation to the seven challenges before the intervention.…”
Section: The Safe-lead Projectmentioning
confidence: 99%
See 2 more Smart Citations